ChemInform Abstract: Catalyst‐Free Dehydrative α‐Alkylation of Ketones with Alcohols: Green and Selective Autocatalyzed Synthesis of Alcohols and Ketones. Issue 28 (15th July 2014) - Xu, Qing; Chen, Jianhui; Tian, Haiwen; Yuan, Xueqin; Li, Shuangyan; Zhou, Chongkuan; Liu, Jianping
Abstract The title syntheses of alcohols and ketones proceed in a one‐pot manner and on a large scale by C=C bond formation of the in situ generated intermediates with subsequent selective Meerwein—Pondorf—Verley—Oppenauer‐type redox processes.